Reading Revelation from the top or the underside - De Villiers, Pieter GR (Stellenbosch Theological Journal, 2017)
I dedicate this article to Allan Boesak on the occasion of his 70th birthday in appreciation of his fearless struggle against racism, but also in gratitude for his many other writings in which he consistently promoted the cause of oppressed, vilified and abused groups in society in a truly compassionate and inspiring manner. This article also wishes to give recognition to his singular contribution to the study of Revelation, reflected in the many references to his commentary in scholarly works (cf. part 3 below).